去括号:(1).-(x-1)=(2).2(-a+1/2b)=(3).-1/2(y-2z)=(4)-0.2(5*5x+1)=

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/22 20:41:38
去括号:(1).-(x-1)=(2).2(-a+1/2b)=(3).-1/2(y-2z)=(4)-0.2(5*5x+1)=
x){ڷYaQki~O=zFچFI@Y SRר 55ʛjVhu$飘@2b.D1t lb$t# q9R(Q; KAJ*V5 $فs

去括号:(1).-(x-1)=(2).2(-a+1/2b)=(3).-1/2(y-2z)=(4)-0.2(5*5x+1)=
去括号:
(1).-(x-1)=
(2).2(-a+1/2b)=
(3).-1/2(y-2z)=
(4)-0.2(5*5x+1)=

去括号:(1).-(x-1)=(2).2(-a+1/2b)=(3).-1/2(y-2z)=(4)-0.2(5*5x+1)=
(1).-(x-1)=-X+1
(2).2(-a+1/2b)=-2a+b
(3).-1/2(y-2z)=-1/2y+z
(4)-0.2(5*5x+1)= -5x-0.2